Click functionalized biocompatible gadolinium oxide core-shell nanocarriers for imaging of breast cancer cells. Issue 49 (8th November 2022) - Siribbal, Shifaa M.; Ilyas, Shaista; Renner, Alexander M.; Iqbal, Sumiya; Muñoz Vázquez, Sergio; Moawia, Abubakar; Valldor, Martin; Hussain, Muhammad S.; Schomäcker, Klaus; Mathur, Sanjay
Abstract : Site-specific delivery using functionalized nanocarriers is in high demand in imaging applications of modern clinical research. Abstract : Site-specific delivery using functionalized nanocarriers is in high demand in imaging applications of modern clinical research. To improve the imaging capabilities of conventionally used contrast agents and expand the targeting accuracy, functional gadolinium oxide based nanocarriers originated from homogeneous core shells structures (Gd2 O3 @SiO2 @Fe3 O4 ) were developed using a multilayer formation approach. The synthesis and chemical configuration for the covalent binding of macrocyclic chelating agents and estrogen targeting molecules on these nanocarriers were designed by a two-step chemical synthesis method. Initially, SiO2 @Fe3 O4 structures were prepared and encapsulated with a homogenous thin Gd2 O3 overlayer. The exterior surface of the as-prepared carriers offered chemical binding with a breast cancer specific estrogen molecule, covalently grafted through a Click-Chemistry protocol. In the next step, to enhance the diagnostic imaging capabilities of these carriers, thiocyanate-linked chelator molecule, DOTA, was attached to the surface of estrogen bound Gd2 O3 @SiO2 @Fe3 O4 using basic reaction conditions. The active amino groups before and after conjugation of estrogen molecules on the surface were quantified using a fluorescamine based approach. Due to the covalent binding of the macrocyclic chelator to the Gd2 O3 @SiO2 @Fe3 O4 surface, core shell carriers showed potential radiolabeling efficiency using positron emitter radionuclide, gallium-68 ( 68 Ga). Intracellular uptake of estrogen-conjugated carriers was evaluated with MCF7 breast cancer cell lines using confocal laser scanning microscopy and fluorescent flow cytometry. In addition, in vitro cytotoxicity studies of functional nanocarriers as compared to bare nanoparticles showed reduced toxicity to HEK-293 cells demonstrating the role of surface attached molecules in preventing direct exposure of the Gd2 O3 surface to the cells. The as-developed gadolinium based nanocarriers presented excellent capabilities as biocompatible target-specific imaging probes which indicates great potential in the field of dual-mode contrast agents.